Krisis Politik Myanmar : Masa Depan Demokrasi Pasca Kudeta Militer dan Peran Indonesia - Muhamad Adian Firnas; Kiky Rizky (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
The coup that was carried out by military leader General Min Aung Hlaing shocked the international community. This coup was not only a failure of the democratic life that had been developing in the country since 2010, this coup will return Myanmar to the authoritarianism that has been in the country for almost 50 years. This article aims to examine the future of democracy in Myanmar and what Indonesia can do to support democratization in this country.. The method used is descriptive method with secondary data sources This article finds that the continuation of democracy in this country will be difficult based on internal conditions. The military solidity in supporting the coup and the tendency of the junta leader to extend martial law on the grounds of instability and weakening pro-democracy forces with a repressive approach shows that the military still wants to maintain its powers as it did in the past. That opportunity exists precisely from outside the country, namely pressure and involvement from the international community, including Indonesia. The political crisis that has widened into a humanitarian crisis must be used as an entry point for Indonesia to open a dialogue with the military junta. Indonesia's position as chair of ASEAN is a test for Indonesia to bring progress in resolving the political crisis in Myanmar Keywords: Democracy, Military Coup, Humanitarian Intervention